Evaluation the Effect of Stevia Leaves Powder on Antioxidant, Digestive Enzyme and Meat Quality in Broiler Chickens - Zainab Ibrahim; Nameer Khudhair; Measem Ali (Basrah Journal of Veterinary Research)
commercial poultry farming is a rapidly growing sector. therefore, the study Aimed to evaluate the impact of stevia leaf powder on oxidative status and digestion and their reflection on meat quality parameters in broiler Chickens.Materials and methods From December 21, 2023, to January 17, 2024, 240 Ross broiler chicks were given different Stevia leaf powder dosages. Four groups of Babylon's Modern Al-Bakri Hatchery chicks received different treatments for 28 days. Group 1 (control) got a conventional diet, while Groups 2, 3, and 4 received diets supplemented with 10 g/kg, 20 g/kg, and 30 g/kg Stevia leaf powder. Locally ground stevia was added to the diet. The study examined digestive enzyme levels, antioxidant activity, and meat quality in broiler chickens treated with varied Stevia leaf powder (STV) concentrations. The STV-treated groups had significantly higher amylase levels (p≤ 0.05) than the control group, with no significant variations across STV concentrations. The 30g/kg STV group had slightly increase in lipase levels, but otherwise no changes. Compared to other groups, the 20g/kg STV group had considerably greater antioxidant enzyme activity, including SOD, CAT, and GLUpx. Chickens treated with 10g/kg had higher antioxidant activity, but the group did not vary from control. STV supplementation reduced meat pH, which improves tenderness and shelf life, and slightly increased cooking loss. The 20g/kg STV group showed decreased drip loss, indicating greater water retention and meat quality.